Pengaruh Padat Tebar Berbeda terhadap Pertumbuhan dan Kelangsungan Hidup Benih Ikan Koi (Cyprinus Carpio) di Kelompok Tani “Budidaya Ikan Hias Sekojo” - Anggraini, Lola; Tanbiyaskur, Tanbiyaskur; Nadhira, Lutfi Rafi; Dwi Yanti, Anglie; Punagari, Mutiara; Anggelina, Lilis; Ramadhon, M. Farhan (Seminar Nasional Lahan Suboptimal, 2023)
Anggraini, L., Tanbiyaskur., Nadhira, L.R., Yanti, A.D., Punagari, M., Anggelina, L., Ramadhon, M.F. (2023). The effect of probiotics in commercial feed on the growth of sangkuriang catfish (Clarias gariepinus). In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-11 Tahun 2023, Palembang  21 Oktober 2023. (pp. 192-198).  Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI). Koi fish are one of the ornamental fish that have cultivation prospects that are in great demand. One of the factors that influences koi fish cultivation is stocking density, high stocking density can have an impact on the growth rate and survival of koi fish. Fish density influences cultivation which can cause competition for food and space for fish to move which can affect fish growth. The aimed of this experiment is to determine the optimal stocking density for the growth and survival of koi fish seeds. This experiment used 2 treatments, namely P1 (stocking density of 200 individuals m2) and P2 (stocking density of 150 individuals m2). The results obtained in treatment (P1) with a stocking density of 200 individuals m2 were growth in length and absolute weight of 1.32 cm and 3.08 g and survival was 100%. The temperature during the maintenance period ranged from 27-28oC and the pH during the maintenance period was found to be around 6.5-7.9. It can be concluded that (P1) with a stocking density of 200 m2 is the best treatment for growth in absolute length and weight, survival and water quality during maintenance at a stocking density of koi fish.